Arterial Vascularization of Prostata in the Dogs - Yılmaz, Sadık (Van Yüzüncü Yıl Üniversitesi, 1991)
The artery of prostata is a. prostatica. A. prostatica originatesfrom a. pudenda intema which is the branch of a. iliaca intema. After separatingfrom a. pudenda intema, a. prostatica gives the branches such as a. ductus deferentis,a. vesicalis, a. rectalis media and a. urethralis.

Prostata 'nın damari a. prostatica 'dır. A. prostatica a. iliaca interna 'nınkolu olan a. pudenda interna 'dan köken alır. A. prostatica, a. pudenda intema 'dan ayrıldıktan sonra a. ductus deferentis, a. vesicalis caudalis, a. rectalis media ve a.urethralis gibi kollları verir.
KÖPEKLERDE PROSTATA'NIN ARTERİEL VASKULARİZASYONU